A material with anisotropic conductive properties and its preparation method and use

By introducing a nanoporous structural layer of modified oxides and conductive agents into the flexible carbon nanotube film, the graft groups on the surface of the oxide promote the diffusion of conductive agents, the problem of insufficient conductivity of existing carbon nanotube flexible films is solved. , realizes the conductivity of the material in the longitudinal and transverse directions, and improves the heating efficiency.

CN119153152BActive Publication Date: 2025-01-07YISHIWEN BIOTECHNOLOGY (TIANJIN) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411604538.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-01-07
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

The conductivity of existing carbon nanotube flexible films has not been fully utilized, resulting in low heating efficiency and inability to generate heat simultaneously on the inside and on the surface of the material.

Method used

A material structure is adopted including a substrate layer, a nanoporous structural layer and a conductive layer, wherein the nanoporous structural layer is composed of a modified oxide, a conductive agent and a water-soluble polymer resin. The conductive agent is located inside the modified oxide and passes through the oxide. 表面的接枝基团促进导电剂扩散,实现纵向导电能力,并通过毛细作用提升导电层与基材的结合强度。

Benefits of technology

The conductivity of the material in the horizontal and vertical directions is achieved, the heating area is increased, the connection strength and conductivity efficiency between the conductive layer and the substrate are improved, and the material can fully generate heat in the entire space.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the technical field of conductive materials, and discloses a material with anisotropic conductive properties, a preparation method thereof and a use thereof, wherein the material comprises a substrate layer, a nanoporous structure layer and a conductive layer; the nanoporous structure layer is arranged between the substrate layer and the conductive layer; the nanoporous structure layer comprises a modified oxide, and the modified oxide comprises one or more of modified aluminum oxide and modified silicon oxide; the surface of the modified oxide is grafted with one or more modified groups of γ-aminopropyltriethoxysilane, ammonium polyacrylate, diallyldimethylammonium chloride, γ-glycidyloxypropyltrimethylsilane and sodium dodecyl sulfate. The material obtained by the present invention can have conductivity in both horizontal and vertical directions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of conductive materials, and in particular to a material with anisotropic conductive properties, a preparation method and application thereof. Background Art

[0002] With the rapid development of wearable devices and flexible electronic devices, the demand for flexible conductive heating elements is increasing. Carbon nanotubes exhibit a novel heating mechanism: when electricity is turned on, the CC covalent bonds of carbon nanotubes are excited and oscillate. The energy generated by the oscillation radiates outward in the form of phonons, emitting far-infrared electromagnetic waves with a wavelength of 3μm-20μm. Far-infrared waves can radiate directly outward through a transparent substrate without causing energy loss due to phonon scattering. Phonon energy is transmitted in the form of far-infrared, allowing external objects to quickly absorb and heat, realizing a new heating mechanism that heats when power is on and cools when power is off, with an electrothermal conversion efficiency of 99.5%. The many advantages of carbon nanotubes have received widespread attention and have become the main material for preparing flexible conductive heating films.

[0003] However, the existing production methods of carbon nanotube flexible films are usually: (1) forming a carbon nanotube film by calendering; (2) forming a carbon nanotube film by mixing with an adhesive to form a coating liquid and coating it on a substrate. However, the flexible films prepared by these two methods do not fully utilize the conductive properties of the material to generate heat. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a material with anisotropic conductive properties, a preparation method and use thereof. The material obtained by the present invention can have conductivity in both horizontal and vertical directions, which is not only beneficial to the heating of the surface layer of the material, but also the inside of the material can generate heat, thereby increasing the heating area of ​​the material and making the entire material space heated and fully utilized.

[0005] The present invention provides a material for forming anisotropic conductive properties, the material of the present invention comprises a substrate layer, a nanoporous structure layer and a conductive layer;

[0006] The nanoporous structure layer is disposed between the substrate layer and the conductive layer;

[0007] The nanoporous structure layer includes modified oxides, and the modified oxides include one or more of modified aluminum oxide and modified silicon oxide;

[0008] The surface of the modified oxide is grafted with one or more modifying groups selected from the group consisting of gamma-aminopropyltriethoxysilane, ammonium polyacrylate, diallyldimethylammonium chloride, gamma-glycidyloxypropyltrimethylsilane and sodium dodecyl sulfate.

[0009] Furthermore, the nanoporous structure layer also includes a conductive agent, and the conductive agent is located inside the structure of the modified oxide.

[0010] Furthermore, the conductive agent includes one or more of polythiophene and polyaniline.

[0011] Furthermore, the nanoporous structure layer also includes a water-soluble polymer resin.

[0012] Furthermore, the water-soluble polymer resin includes one or more of polyvinyl pyrrolidone, hydroxypropyl cellulose, acrylic resin, and polyvinyl alcohol.

[0013] Furthermore, the conductive layer includes one-dimensional carbon nanotube material.

[0014] Furthermore, the one-dimensional carbon nanotube material includes one or more of single-walled carbon nanotubes, double-walled carbon nanotubes, and multi-walled carbon nanotubes.

[0015] Furthermore, the aspect ratio of the one-dimensional carbon nanotube material is 50-100:1; and the pore size of the modified oxide is 10nm-50nm.

[0016] Furthermore, the diameter of the one-dimensional carbon nanotube material is not less than the pore diameter of the modified oxide.

[0017] Furthermore, the particle size of the modified oxide is 100nm-500nm.

[0018] Furthermore, the substrate layer includes a coatable substrate.

[0019] Furthermore, the coatable substrate includes one of polyethylene terephthalate (PET), polypropylene (PP), polycarbonate (PC), and polyvinyl chloride (PVC).

[0020] Furthermore, the thickness of the substrate layer is 0.02 mm-0.15 mm.

[0021] Furthermore, the thickness of the nanoporous structure layer is 50 μm-100 μm.

[0022] Furthermore, the thickness of the conductive layer is 0.15 μm-4.5 μm.

[0023] The present invention also improves the preparation method of the material forming anisotropic conductive properties, and the preparation method comprises:

[0024] S1: dispersing the one-dimensional carbon nanotube material in a solution, adding a dispersant, and mixing evenly to obtain a conductive layer slurry;

[0025] S2: adjusting the pH value of the modified oxide slurry to 2.5-3.5, adding a water-soluble polymer resin solution, a leveling agent, and a curing agent, and mixing them evenly to obtain a nanoporous structure layer slurry;

[0026] S3: dissolving and dispersing the conductive agent in the solution to obtain a conductive agent dispersion;

[0027] S4: coating the nanoporous structure layer slurry on the surface of the coatable substrate and drying; coating the conductive agent dispersion on the nanoporous structure layer and drying; and continuing to coat the conductive layer slurry and drying.

[0028] Furthermore, the added mass of the dispersant is 1%-5% of the mass of the one-dimensional carbon nanotube material.

[0029] Furthermore, the mass concentration of the one-dimensional carbon nanotube material in the solution is 0.5%-1.5%.

[0030] Furthermore, the solution is deionized water.

[0031] Furthermore, the mass concentration of the conductive agent in the conductive agent dispersion is 0.1%-1%.

[0032] Furthermore, the specific method for adjusting the pH value of the modified oxide slurry to 2.5-3.5 is to use a glacial acetic acid solution with a mass concentration of 10%.

[0033] Furthermore, the preparation method of the glacial acetic acid solution includes mixing glacial acetic acid with deionized water.

[0034] Furthermore, the leveling agent includes one or more of an organic silicon surfactant and a fluorine ion surfactant.

[0035] Furthermore, the organosilicon surfactant includes BYK348.

[0036] Furthermore, the fluorine ion surfactant includes FS-3100.

[0037] Furthermore, the curing agent includes one or more of boric acid, borax, acetaldehyde, and isocyanate.

[0038] Furthermore, the added amount of the leveling agent is 0.1%-2.5% of the total mass of the nanoporous structure layer slurry.

[0039] Furthermore, the added amount of the curing agent is 2%-3% of the water-soluble polymer resin in the water-soluble polymer resin solution.

[0040] Furthermore, the mass concentration of the water-soluble polymer resin solution is 5%-15%.

[0041] Furthermore, the ratio of the modified oxide slurry to the water-soluble polymer resin in the water-soluble polymer resin solution is 1-10:1 by mass.

[0042] Furthermore, the preparation method of the water-soluble polymer resin solution is a conventional method, that is, dissolving and dispersing the water-soluble polymer resin in a solvent. Those skilled in the art should understand that due to the characteristics of the water-soluble polymer resin itself, different solvents are used for dissolution, for example, water, ethanol, etc. Those skilled in the art can select the solvent they need according to the water-soluble polymer resin.

[0043] Furthermore, the drying temperature is 50°C-60°C.

[0044] Furthermore, the preparation method of the modified oxide slurry includes: adding the modifying group to a solution containing an oxide, mixing evenly, performing an aging treatment, and cooling to obtain the modified oxide slurry.

[0045] In the process of modifying the oxide in the present invention, the modifying group reacts with the hydroxyl group on the surface of the oxide to perform condensation, so that the modifying group is grafted on the surface of the oxide, thereby completing the modification process.

[0046] Furthermore, the ratio of the modified group to the oxide is 5:100 by mass.

[0047] Furthermore, the method for preparing the solution containing oxides includes mixing the oxides with deionized water, wherein the ratio of the oxides to the deionized water is 1:4 by mass.

[0048] Furthermore, there are many ways to achieve uniform mixing. In the present invention, as an example, a high shear disperser can be used for shearing treatment at 8000 rpm for 60 minutes.

[0049] Furthermore, the specific method of the aging treatment is: treating at 70°C-90°C for 230min-250min.

[0050] Furthermore, stirring may be performed during the aging process.

[0051] The present invention also provides the use of the material forming anisotropic conductive properties, and the material having anisotropic conductive properties is used for physical therapy electrode sheets, wearable heating clothing, wall heating paintings, and glass defrosting films.

[0052] The embodiments of the present invention have the following technical effects:

[0053] 1. In the present invention, the grafted groups on the oxide in the nanoporous structure layer can promote the diffusion of the conductive agent into the modified oxide, thereby realizing the conductivity of the material of the present invention in the longitudinal direction; and in the present invention, first, the porous structure of the oxide can adsorb the conductive layer and the substrate layer by capillary action, and the bidirectional connection performance improves the bonding strength between the conductive layer and the substrate, thereby improving the connection strength between the conductive layer and the substrate layer and the nanoporous structure layer, and second, the water-soluble polymer resin can also improve the connection strength between the conductive layer and the substrate. In addition, the grafted groups on the surface of the oxide can also reduce the agglomeration of the oxide nanoparticles, increase the uniformity of the nanoparticles in the polymer resin, and thus facilitate the acquisition of a uniform nanoporous structure layer slurry.

[0054] 2. In the present invention, in order to further enhance the adsorption effect of the modified oxide in the nanoporous structure layer on the conductive agent, grafts that can cooperate with the conductive agent are designed on the oxide surface according to different conductive agents; and the grafting amount on the oxide surface is further selected to enhance the adsorption capacity of the oxide on the dispersant while preventing the grafts from being entangled with each other. DETAILED DESCRIPTION

[0055] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.

[0056] In a first aspect, some embodiments of the present invention provide a material for forming anisotropic conductive properties, the material of the present invention comprising a substrate layer, a nanoporous structure layer and a conductive layer;

[0057] The nanoporous structure layer is disposed between the substrate layer and the conductive layer;

[0058] The nanoporous structure layer includes modified oxides, and the modified oxides include one or more of modified aluminum oxide and modified silicon oxide;

[0059] The surface of the modified oxide is grafted with one or more modifying groups selected from the group consisting of γ-aminopropyltriethoxysilane, ammonium polyacrylate, diallyldimethylammonium chloride, γ-glycidyloxypropyltrimethylsilane, and sodium dodecyl sulfate;

[0060] The nanoporous structure layer further includes a conductive agent, which is located inside the structure of the modified oxide.

[0061] In some embodiments, the conductive agent includes one or more of polythiophene and polyaniline.

[0062] In some embodiments, the nanoporous structure layer further includes a water-soluble polymer resin.

[0063] In some embodiments, the water-soluble polymer resin includes one or more of polyvinyl pyrrolidone, hydroxypropyl cellulose, acrylic resin, and polyvinyl alcohol.

[0064] In some embodiments, the conductive layer includes a one-dimensional carbon nanotube material.

[0065] In some embodiments, the one-dimensional carbon nanotube material includes one or more of single-walled carbon nanotubes, double-walled carbon nanotubes, and multi-walled carbon nanotubes.

[0066] In some embodiments, the aspect ratio of the one-dimensional carbon nanotube material is 50-100:1; and the pore size of the modified oxide is 10nm-50nm.

[0067] In some embodiments, the diameter of the one-dimensional carbon nanotube material is not less than the pore diameter of the modified oxide.

[0068] In some embodiments, the particle size of the modified oxide is 100 nm-500 nm.

[0069] In some embodiments, the substrate layer comprises a coatable substrate.

[0070] In some embodiments, the coatable substrate includes one of polyethylene terephthalate (PET), polypropylene (PP), polycarbonate (PC), and polyvinyl chloride (PVC).

[0071] In some embodiments, the thickness of the substrate layer is 0.02 mm-0.15 mm.

[0072] In some embodiments, the thickness of the nanoporous structure layer is 50 μm-100 μm.

[0073] In some embodiments, the thickness of the conductive layer is 0.15 μm-4.5 μm.

[0074] In a second aspect, some embodiments of the present invention further provide a method for preparing the material having anisotropic conductive properties, the method comprising:

[0075] S1: dispersing the one-dimensional carbon nanotube material in a solution, adding a dispersant, and mixing evenly to obtain a conductive layer slurry;

[0076] S2: adjusting the pH value of the modified oxide slurry to 2.5-3.5, adding a water-soluble polymer resin solution, a leveling agent, and a curing agent, and mixing them evenly to obtain a nanoporous structure layer slurry;

[0077] S3: dissolving and dispersing the conductive agent in the solution to obtain a conductive agent dispersion;

[0078] S4: coating the nanoporous structure layer slurry on the surface of the coatable substrate and drying; coating the conductive agent dispersion on the nanoporous structure layer and drying; and continuing to coat the conductive layer slurry and drying.

[0079] In some embodiments, the added mass of the dispersant is 1%-5% of the mass of the one-dimensional carbon nanotube material.

[0080] In some embodiments, the mass concentration of the one-dimensional carbon nanotube material in the solution is 0.5%-1.5%.

[0081] In some embodiments, the solution is deionized water.

[0082] In some embodiments, the mass concentration of the conductive agent in the conductive agent dispersion is 0.1%-1%.

[0083] In some embodiments, the specific method of adjusting the pH value of the modified oxide slurry to 2.5-3.5 is: using a glacial acetic acid solution with a mass concentration of 10%.

[0084] In some embodiments, the method for preparing the glacial acetic acid solution includes mixing glacial acetic acid with deionized water.

[0085] In some embodiments, the leveling agent includes one or more of an organic silicon surfactant and a fluorine ion surfactant.

[0086] In some embodiments, the organosilicon surfactant includes BYK348.

[0087] In some embodiments, the fluoride ion surfactant includes FS-3100.

[0088] In some embodiments, the curing agent includes one or more of boric acid, borax, acetaldehyde, and isocyanate.

[0089] In some embodiments, the amount of the leveling agent added is 0.1%-2.5% of the total mass of the nanoporous structure layer slurry.

[0090] In some embodiments, the curing agent is added in an amount of 2%-3% of the water-soluble polymer resin.

[0091] In some embodiments, the mass concentration of the water-soluble polymer resin solution is 5%-15%.

[0092] In some embodiments, the ratio of the modified oxide slurry to the water-soluble polymer resin in the water-soluble polymer resin solution is 1-10:1 by mass.

[0093] In some embodiments, the drying temperature is 50°C-60°C.

[0094] In some embodiments, the method for preparing the modified oxide slurry includes: adding the modifying group to a solution containing an oxide, mixing evenly, performing an aging treatment, and cooling to obtain a modified alumina slurry.

[0095] In some embodiments, the ratio of the modified group to the oxide is 5:100 by mass.

[0096] In some embodiments, the method for preparing the solution containing oxides includes mixing the oxides with deionized water, wherein the ratio of the oxides to the deionized water is 1:4 by mass.

[0097] In some embodiments, the specific method of the aging treatment is: treating at 70° C.-90° C. for 230 min-250 min.

[0098] In some embodiments, stirring may be performed during the aging process.

[0099] In a third aspect, some embodiments of the present invention also provide uses of the material having anisotropic conductive properties, wherein the material having anisotropic conductive properties is used for physiotherapy electrodes, wearable heating clothing, wall heating paintings, and glass defrosting films.

[0100] The following is further described in conjunction with specific embodiments and comparative examples.

[0101] Example 1

[0102] (1) Nanoporous structure layer:

[0103] Prepare modified alumina slurry: Alumina and deionized water are mixed in a mass ratio of 1:4, γ-glycidyloxypropyltrimethylsilane is added, and the mass ratio of γ-glycidyloxypropyltrimethylsilane to alumina is = 5:100, and a high shear disperser is sheared at 8000 rpm for 60 minutes, and then the above dispersion is placed in a three-necked bottle, stirred and aged at 85°C for 240 minutes, and naturally cooled for use;

[0104] Weigh 35.3g of the prepared modified alumina slurry, adjust the pH to 2.5-3.5 with a 10% glacial acetic acid dilute solution, and stir for half an hour until the powder is evenly dispersed and in a translucent sol state; 39.22g of polyvinyl alcohol PVA235 solution, wherein the mass concentration of polyvinyl alcohol PVA235 in the polyvinyl alcohol PVA235 solution is 9%; stir for half an hour and mix evenly; then add 1.8g of leveling agent BYK348 and 0.1g of curing agent boric acid, stir for 15 minutes, mix evenly, and obtain a nanoporous structure layer slurry;

[0105] The nanoporous structure layer slurry was coated on the PET substrate with a coating rod and placed in a 55°C forced air drying oven for drying. The tested coating thickness was 20.4 μm.

[0106] (2) Conductive agent dispersion:

[0107] Adding polythiophene into deionized water to prepare a conductive agent dispersion with a mass concentration of 1%;

[0108] The conductive agent dispersion is coated on the nanoporous structure layer with a coating rod and placed in a 55°C forced air drying oven for drying;

[0109] (3) Conductive layer:

[0110] 8 g of multi-walled carbon nanotubes were added to 1000 mL of deionized water, 5% of dodecylbenzenesulfonic acid dispersant was added, and the mixture was emulsified and dispersed by a high-speed emulsifier to prepare a conductive layer slurry;

[0111] The conductive layer slurry was coated on the nanoporous structure layer with a coating rod and placed in a 55° C. forced air drying oven for drying. The conductive layer thickness was tested to be 0.15 μm.

[0112] Example 2

[0113] The preparation method is the same as that of Example 1, but the modifying group used in Example 2 is sodium dodecyl sulfate, and the other methods are the same as those of Example 1.

[0114] Example 3

[0115] The preparation method is the same as that of Example 1, but in Example 3, not only aluminum oxide but also silicon oxide is used, wherein the mass ratio of aluminum oxide to silicon oxide is 5:1, and the modified group used is ammonium polyacrylate, and the other methods are the same as those of Example 1.

[0116] Example 4

[0117] The preparation method is the same as that in Example 1, but in Example 4, not only aluminum oxide but also silicon oxide is used, wherein the mass ratio of aluminum oxide to silicon oxide is 1:1, and the modifying group used is γ-aminopropyltriethoxysilane, and the other methods are the same as those in Example 1.

[0118] Comparative Example 1:

[0119] The preparation method is the same as that of Example 4, but silicon oxide and aluminum oxide are not grafted. Other methods are the same as those of Example 4.

[0120] Comparative Example 2:

[0121] The preparation method is the same as that of Example 1, but no grafted oxide is added in the preparation of the nanoporous structure layer. Other preparation methods are the same as those of Example 1.

[0122] The embodiments and comparative examples were tested:

[0123] (1) Transverse current test method: Cut the carbon nanotube conductive film prepared by the above scheme into a 30.0 mm × 50.0 mm rectangular narrow strip; fix it using a solid-state adjustable DC voltage-regulated power supply and a 30.0 mm wide electrode test fixture. After stabilization for 5 seconds, read the current value at the corresponding voltage of the voltage regulator.

[0124] (2) Longitudinal current test method: The carbon nanotube conductive film prepared by the above scheme is cut into 30.0 mm × 50.0 mm rectangular narrow strips; a solid-state adjustable DC voltage-stabilized power supply and a pointed electrode are fixed to two points on the front and back sides of the conductive film. After stabilization for 5 seconds, the current value under the corresponding voltage of the voltage regulator is read.

[0125] Results and Analysis:

[0126] Table 1 Test results of embodiments and comparative examples

[0127]

[0128] A material with anisotropic conductive properties is successfully obtained by the method of the present invention. In the present invention, the grafted groups on the oxide in the nanoporous structure layer can promote the diffusion of the conductive agent into the modified oxide, thereby realizing that the material of the present invention has conductivity in the longitudinal direction. It can be verified by comparing Examples 1 to 4 with Comparative Examples 1 and 2 that the material obtained in the present invention has conductivity in both the transverse and longitudinal directions. The conductivity in both the horizontal and vertical directions is not only conducive to the heating of the surface layer of the material, but also the heating of the interior of the material, increasing the heating area of ​​the material, so that the space of the entire material is heated and fully utilized.

[0129] By grafting different modified groups on the oxide, the oxide is enabled to adsorb the conductive agent, thereby achieving the vertical conductivity of the material of the present invention. When the number of groups grafted with aluminum oxide is different, the modification effect on the oxide will be different. When the number of grafts is too large, it may cause entanglement between the grafted chains, and the adsorption capacity will decrease, which may cause the vertical conductivity to decrease; and when the number of grafts is small or no grafting, it may cause incomplete modification of the oxide, and the conductive agent cannot be adsorbed. Therefore, the grafting number is within a suitable range, which can not only enhance the adsorption of the oxide on the conductive agent, but also be beneficial to its vertical conductivity. Therefore, in the present invention, the ratio of the modified group to the oxide is 5:100 by mass.

[0130] On this basis, it should be understood by those skilled in the art that the oxide surface grafted groups can enhance the adsorption effect of the oxide on the conductive agent, mainly due to the interaction between the oxide surface grafted groups and the conductive agent. Only when the grafted groups find a conductive agent that can match with it, can it have a better adsorption effect. It can be verified by comparing Example 1 and Example 2 that when the grafted group is sodium dodecyl sulfate, it has a better adsorption effect on thiophene, and the obtained material has better conductivity in the horizontal and vertical directions. Therefore, it is further preferred that when the grafted group is sodium dodecyl sulfate, the conductive agent selects thiophene.

[0131] The grafted oxides were further studied. As shown in the comparison between Example 3 and Example 4, Example 3 has better conductivity in the vertical and horizontal directions. It is speculated that this is because aluminum oxide is the main component and silicon oxide is the additive. The richer pore structure of silicon oxide improves the pore structure of the material in both the horizontal and vertical directions, and more conductive agents are adsorbed, so the current becomes larger. As silicon oxide increases and aluminum oxide decreases, the conductivity in the horizontal and vertical directions will weaken and decrease. This may be because the positive charge on the surface of aluminum oxide has an adhesion and fixing effect on the negatively charged carbon nanotubes, and the reduction of aluminum oxide causes the connection ability with the conductive layer to decrease, which in turn affects the final conductivity of the material. It is further preferred that the mass ratio of modified silicon oxide and modified aluminum oxide in the modified oxide is 1:5.

[0132] It should be noted that the terms used in the present invention are only for describing specific embodiments, rather than limiting the scope of the present application. As shown in the present specification, unless the context clearly indicates an exception, the words "one", "a", "a kind of" and / or "the" do not specifically refer to the singular, but may also include the plural. The terms "include", "comprise" or any other variant thereof are intended to cover non-exclusive inclusion, so that the process, method or device including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method or device. In the absence of more restrictions, the elements defined by the sentence "include one..." do not exclude the presence of other identical elements in the process, method or device including the elements.

[0133] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the technical solutions of the embodiments of the present invention.

Claims

1. A material having anisotropic conductive properties, characterized in that: The material comprises a substrate layer, a nanoporous structure layer and a conductive layer; The nanoporous structure layer is disposed between the substrate layer and the conductive layer; The nanoporous structure layer includes modified oxides, and the modified oxides include one or more of modified aluminum oxide and modified silicon oxide; The surface of the modified oxide is grafted with one or more modifying groups selected from γ-aminopropyltriethoxysilane, ammonium polyacrylate, diallyldimethylammonium chloride, γ-glycidyloxypropyltrimethylsilane, and sodium dodecyl sulfate; the nanoporous structure layer also includes a conductive agent, which is located inside the structure of the modified oxide.

2. The material according to claim 1, characterized in that The conductive agent includes one or more of polythiophene and polyaniline; The nanoporous structure layer also includes a water-soluble polymer resin; The water-soluble polymer resin includes one or more of polyvinyl pyrrolidone, hydroxypropyl cellulose, acrylic resin, and polyvinyl alcohol.

3. The material according to claim 1, characterized in that The conductive layer includes a one-dimensional carbon nanotube material; The aspect ratio of the one-dimensional carbon nanotube material is 50-100:1; the pore size of the modified oxide is 10nm-50nm; The diameter of the one-dimensional carbon nanotube material is not less than the pore diameter of the modified oxide.

4. The method for preparing the material with anisotropic conductive properties according to any one of claims 1 to 3, characterized in that: The preparation method comprises: S1: dispersing the one-dimensional carbon nanotube material in a solution, adding a dispersant, and mixing evenly to obtain a conductive layer slurry; S2: adjusting the pH value of the modified oxide slurry to 2.5-3.5, adding a water-soluble polymer resin solution, a leveling agent, and a curing agent, and mixing them evenly to obtain a nanoporous structure layer slurry; S3: dissolving and dispersing the conductive agent in the solution to obtain a conductive agent dispersion; S4: coating the nanoporous structure layer slurry on the surface of the coatable substrate and drying; coating the conductive agent dispersion on the nanoporous structure layer and drying; and continuing to coat the conductive layer slurry and drying.

5. The preparation method according to claim 4, characterized in that: The added mass of the dispersant is 1%-5% of the mass of the one-dimensional carbon nanotube material; The mass concentration of the one-dimensional carbon nanotube material in the solution is 0.5%-1.5%; The mass concentration of the conductive agent in the conductive agent dispersion is 0.1%-1%; The ratio of the modified oxide slurry to the water-soluble polymer resin in the water-soluble polymer resin solution is 1-10:1 by mass.

6. The preparation method according to claim 4, characterized in that: The specific method for adjusting the pH value of the modified oxide slurry to 2.5-3.5 is: using a glacial acetic acid solution with a mass concentration of 10%.

7. The preparation method according to claim 4, characterized in that: The leveling agent includes one or more of an organic silicon surfactant and a fluorine ion surfactant; The curing agent includes one or more of boric acid, borax, acetaldehyde, and isocyanate; The amount of the leveling agent added is 0.1%-2.5% of the total mass of the nanoporous structure layer slurry; The amount of the curing agent added is 2%-3% of the water-soluble polymer resin in the water-soluble polymer resin solution; The mass concentration of the water-soluble polymer resin solution is 5%-15%; The drying temperature is 50°C-60°C.

8. The preparation method according to claim 4, characterized in that: The preparation method of the modified oxide slurry comprises: adding the modified group into a solution containing oxides, mixing evenly, performing aging treatment, and cooling to obtain the modified oxide slurry.

9. The preparation method according to claim 8, characterized in that: The ratio of the modified group to the oxide is 5:100 by mass; The method for preparing the solution containing oxides comprises mixing the oxides with deionized water, wherein the ratio of the oxides to the deionized water is 1:4 by mass; The specific method of the aging treatment is: treating at 70°C-90°C for 230min-250min.

10. Use of the anisotropic conductive material according to any one of claims 1 to 3 or the anisotropic conductive material obtained by the preparation method according to any one of claims 4 to 9, characterized in that: The material with anisotropic conductive properties is used for physical therapy electrode sheets, wearable heating clothing, wall heating paintings, and glass defrosting films.

Citation Information

Patent Citations

  • Halogen-free flame-retardant thermoplastic polyurethane elastomer composition and preparation method thereof

    CN103665828A

  • High-hardness corrosion-resistant synthetic resin and preparation method thereof

    CN113088038A